\(\sqrt{20}.\sqrt{72}.\sqrt{4,9}\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

20 tháng 6 2017

\(\sqrt{20}\cdot\sqrt{72}\cdot\sqrt{4,9}\)

\(=\sqrt{7056}\)

\(=84\)

20 tháng 6 2017

\(\sqrt{20}.\sqrt{72}.\sqrt{4,9}=\sqrt{20.72.4,9}=\sqrt{7056}=84\)

11 tháng 8 2016

\(\sqrt{20}\cdot\sqrt{72}\cdot\sqrt{4,9}=\sqrt{20\cdot72\cdot4,9}=\sqrt{2\cdot10\cdot72\cdot4,9}\\ =\sqrt{144\cdot49}=\sqrt{144}\cdot\sqrt{49}=12\cdot7=84\)

Bài 2:

a) \(\sqrt{3a^3}\cdot\sqrt{12a}=\sqrt{3a^3\cdot12a}=\sqrt{36a^4}=6a^2\)

b) \(\sqrt{2a\cdot32ab^2}=\sqrt{64a^2b^2}=8ab\)

15 tháng 7 2016

a. =\(\sqrt{20.72.4,9}=\sqrt{2.72.49}=\sqrt{144.49}=12.7=84\)

b. \(\sqrt{\frac{999}{111}}=\sqrt{9}=3\)

c. = \(\sqrt{9472+27256}=\sqrt{36728}\approx191,645\)

d. = \(\sqrt{\frac{\left(149+76\right)\left(149-76\right)}{\left(457+348\right)\left(457-348\right)}}=\sqrt{\frac{225.73}{805.109}}=\sqrt{\frac{3285}{17549}}\approx136,817\)

5 tháng 7 2017

a, \(5\sqrt{\dfrac{1}{5}}+\dfrac{1}{2}\sqrt{20}+\sqrt{5}\)

\(=\sqrt{5}+\dfrac{1}{2}.2\sqrt{5}+\sqrt{5}\)

\(=3\sqrt{5}\)

b, \(\sqrt{\dfrac{1}{2}}+\sqrt{4,5}+\sqrt{12,5}\)

\(=\sqrt{0,5}+3\sqrt{0,5}+5\sqrt{0,5}=9\sqrt{0,5}\)

c, \(\sqrt{20}-\sqrt{45}+3\sqrt{18}+\sqrt{72}\)

\(=2\sqrt{5}-3\sqrt{5}+3\sqrt{18}+2\sqrt{18}\)

\(=-\sqrt{5}+5\sqrt{18}\)

d, \(0,1.\sqrt{200}+2\sqrt{0,08}+0,4\sqrt{50}\)

\(=\sqrt{0,01.200}+0,2.\sqrt{2}+0,4.5\sqrt{2}\)

\(=\sqrt{2}+0,2\sqrt{2}+2\sqrt{2}=3,2\sqrt{2}\)

Chúc bạn học tốt!!!

23 tháng 4 2017

a, \(3\sqrt{5}\)

b, \(\dfrac{9\sqrt{2}}{2}\)

c, \(15\sqrt{2}-\sqrt{5}\)

d, \(\dfrac{17\sqrt{2}}{5}\)

11 tháng 7 2018

\(a.\sqrt{200}-\sqrt{32}+\sqrt{72}=10\sqrt{2}-4\sqrt{2}+6\sqrt{2}=12\sqrt{2}\)

\(b.\sqrt{175}-\sqrt{112}+\sqrt{63}=5\sqrt{7}-4\sqrt{7}+3\sqrt{7}=4\sqrt{7}\)

\(c.4\sqrt{20}-3\sqrt{125}+5\sqrt{45}-15\sqrt{\dfrac{1}{5}}=8\sqrt{5}-15\sqrt{5}+15\sqrt{5}-3\sqrt{5}=5\sqrt{5}\)

a: \(=10\sqrt{2}-4\sqrt{2}+6\sqrt{2}=12\sqrt{2}\)

b: \(=5\sqrt{7}-4\sqrt{7}+3\sqrt{7}=4\sqrt{7}\)

c: \(=\dfrac{3}{2}\sqrt{6}+\dfrac{2}{3}\sqrt{6}-2\sqrt{6}=\dfrac{1}{6}\sqrt{6}\)

d: \(=8\sqrt{5}-15\sqrt{5}+15\sqrt{5}-3\sqrt{5}=5\sqrt{5}\)

e: \(=\sqrt{5}+\dfrac{2}{5}\sqrt{5}+\sqrt{5}=2.4\sqrt{5}\)

f: \(=\dfrac{1}{5}\sqrt{5}+\dfrac{3}{2}\sqrt{2}+\dfrac{5}{2}\sqrt{2}=\dfrac{1}{5}\sqrt{5}+4\sqrt{2}\)

1 tháng 8 2018

1, \(\sqrt{8}-3\sqrt{32}+\sqrt{72}=2\sqrt{2}-12\sqrt{2}+6\sqrt{2}=-4\sqrt{2}\)

2,\(6\sqrt{12}-2\sqrt{48}+5\sqrt{75}-7\sqrt{108}=12\sqrt{3}-8\sqrt{3}+25\sqrt{3}-42\sqrt{3}=-13\sqrt{3}\)

3, \(\sqrt{20}+3\sqrt{45}-6\sqrt{80}-\dfrac{1}{3}\sqrt{125}=2\sqrt{5}+9\sqrt{5}-24\sqrt{5}-\dfrac{5}{3}.\sqrt{5}=-\dfrac{44}{3}.\sqrt{5}\)

4, \(2\sqrt{5}-\sqrt{125}-\sqrt{80}=2\sqrt{5}-5\sqrt{5}-4\sqrt{5}=-7\sqrt{5}\)

5, \(3\sqrt{2}-\sqrt{8}+\sqrt{50}-4\sqrt{32}=3\sqrt{2}-2\sqrt{2}+5\sqrt{2}-16\sqrt{2}=-10\sqrt{2}\)

2 tháng 8 2018

Thank bạn nhìu nha!!!yeu